Maxwell's handbook for RDA, resource description & access : explaining and illustrating RDA: resource description and access using MARC21 - Maxwell, Robert L., 1957- (Chicago : ALA Editions, an imprint of the American Library Association, 2013)
This comprehensive handbook illustrates and applies the new cataloging rules in the MARC21 environment for every type of information format -- from books to electronic materials to music and beyond.
Introduction -- Describing manifestations and items -- Describing persons -- Describing families -- Describing corporate bodies -- Describing geographic entities -- Describing works -- Describing expressions -- Recording relationships -- Appendix A. Printed books and sheets -- Appendix B. Cartographic resources -- Appendix C. Unpublished manuscripts and manuscript collections -- Appendix D. Notated music -- Appendix E. Audio recordings -- Appendix F. Moving image resources -- Appendix G. Two-dimensional graphic resources -- Appendix H. Three-dimensional resources and objects -- Appendix I. Digital resources -- Appendix J. Microform resources -- Appendix K. Bibliographic records serials and integrating resources -- Appendix L. Analytical description.
Includes bibliographical references and index.
oif 23/06/15
Loan
Keywords: Resource description & access -- Handbooks, manuals, etc; Descriptive cataloging -- Standards -- Handbooks, manuals, etc; Cataloging -- methods -- Handbooks